Law and Word Order: NLP in Legal Tech. (19th December 2018) - DALE, ROBERT
Abstract: The law has language at its heart, so it's not surprising that software that operates on natural language has played a role in some areas of the legal profession for a long time. But the last few years have seen an increased interest in applying modern techniques to a wider range of problems, so I look here at how natural language processing is being used in the legal sector today.